Efektivitas Aplikasi Akuntansi Dan Self – Control Dalam Penyusunan Laporan Keungan UMKM - Talla, Alend; Batkunde, Adonia Anita (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This research is motivated by the low quality of financial reporting among MSMEs in Ambon City, which is caused by limited technological understanding and low discipline among business owners. The research gap lies in the lack of studies that simultaneously examine the influence of accounting application effectiveness and self-control on financial statement preparation, particularly in MSMEs located in Eastern Indonesia. This study aims to test and analyze the combined effect of these two variables. A quantitative approach was employed using the Partial Least Squares (PLS) method. Primary data were collected through questionnaires distributed to 70 MSME actors in Ambon City who had used accounting applications. The test results show that the effectiveness of accounting applications has a significant influence on financial reporting, with a T-statistic value of 4.464 and a P-value of 0.000. Self-control also has a significant effect, with a T-statistic value of 2.477 and a P-value of 0.014. The reliability test results show that the Composite Reliability values for each construct are above 0.93. The conclusion of this study is that the combination of accounting technology and self-control plays an important role in improving the quality of MSME financial reporting. The practical implication is the need to enhance digital literacy and behavioral awareness among business owners to ensure the optimal and sustainable use of technology.